THE EFFECTIVENESS OF THE STUDENT BASIC LITERACY-BASED GRAPHOLOGY SYSTEM (SINGO MBOIS) AT MALANG PUBLIC JUNIOR HIGH SCHOOL 27 IN SUPPORTING THE SCHOOL’S LITERACY PROGRAM - Rifany Arie Yudanti; Raditya Pratama (Four Son Scholarship, 2026)
This study aims to analyze the effectiveness of the Graphology System Based on Students' Basic Literacy (SINGO MBOIS) in supporting the School Literacy Program at SMP Negeri 27 Malang. Basic literacy, including reading, writing, and listening skills, plays an essential role in students’ learning success. This research employed a quantitative descriptive approach with data collected through questionnaires distributed to 288 students from grades VII, VIII, and IX. The instrument used a Likert scale to measure students’ responses across several literacy indicators. Data analysis was conducted using percentage calculations to determine the level of effectiveness. The results show that the average effectiveness of the SINGO MBOIS program reached 76%, categorized as high. Most indicators, such as reading comprehension, writing ability, and learning motivation, demonstrated positive outcomes. However, aspects such as handwriting neatness and audio-based listening still require improvement. Overall, the SINGO MBOIS system is effective in enhancing students’ literacy skills and can be considered an innovative approach to strengthening literacy programs in schools.